Integrated Analysis of Physiological, mRNA Sequencing, and miRNA Sequencing Data Reveals a Specific Mechanism for the Response to Continuous Cropping Obstacles in Pogostemon cablin Roots - Yan, Wuping; Cao, Shijia; Wu, Yougen; Ye, Zhouchen; Zhang, Chan; Yao, Guanglong; Yu, Jing; Yang, Dongmei; Zhang, Junfeng (Frontiers in Plant Science, 2022)
Pogostemon cablin (patchouli) is a commercially important medicinal and industrial crop grown worldwide for its medicinal and aromatic properties. Patchoulol and pogostone, derived from the essential oil of patchouli, are considered valuable components in the cosmetic and pharmaceutical industries. Due to its high application value in the clinic and industry, the demand for patchouli is constantly growing. Unfortunately, patchouli cultivation has suffered due to severe continuous cropping obstacles, resulting in a significant decline in yield and quality. Moreover, the physiological and transcriptional changes in patchouli in response to continuous cropping obstacles remain unclear. This has greatly restricted the development of the patchouli industry. To explore the mechanism underlying the rapid response of patchouli roots to continuous cropping stress, integrated analysis of the transcriptome and miRNA profiles of patchouli roots under continuous and noncontinuous cropping conditions in different growth periods was conducted using RNA sequencing (RNA-seq) and miRNA-seq and complemented with physiological data. The physiological and biochemical results showed that continuous cropping significantly inhibited root growth, decreased root activity, and increased the activity of antioxidant enzymes (superoxide dismutase, peroxidase, catalase) and the levels of osmoregulators (malondialdehyde, soluble protein, soluble sugar, proline). Subsequently, we found 4238, 3494, and 7290 upregulated and 4176, 3202, and 8599 downregulated differentially expressed genes (DEGs) in the three growth periods of continuously cropped patchouli, many of which were associated with primary carbon and nitrogen metabolism, defense responses, secondary metabolite biosynthesis and transcription factors. Based on miRNA-seq, 927 known miRNAs and 130 novel miRNAs were identified, among which 67 differentially expressed miRNAs (DEMIs) belonging to 24 miRNA families were induced or repressed by continuous cropping. By combining transcriptome and miRNA profiling, we obtained 47 miRNA-target gene pairs, consisting of 18 DEMIs and 43 DEGs, that likely play important roles in the continuous cropping response of patchouli. The information provided in this study will contribute to clarifying the intricate mechanism underlying the patchouli response to continuous cropping obstacles. In addition, the candidate miRNAs and genes can provide a new strategy for breeding continuous cropping-tolerant patchouli.